2022
DOI: 10.1016/j.vacun.2021.07.005
|View full text |Cite|
|
Sign up to set email alerts
|

Disposición a recibir la vacuna contra COVID-19 en población de 80 y más años en Colombia 2021

Abstract: Objetivo: Colombia diseñó y adoptó un plan de vacunación contra COVID-19. El objetivo de esta investigación fue conocer su disposición para aceptar la vacunación contra COVID-19 en personas de 80 y más años. Métodos: Se realizó una encuesta telefónica a 11.721 personas de 80 y más años, afiliados a una aseguradora de salud en la que se indagó sobre la disponibilidad a recibir la vacuna. Los respondientes fueron los afiliados o sus familiares o cuidadores. Resultados. El promedio de edad f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…After the elimination of duplicate studies, we assessed the titles and abstracts of the 434 remaining studies, and 401 articles were eliminated because they did not match the selection criteria. A total of 33 studies were read in full-text and 19 studies were included in the qualitative synthesis and 18 in the quantitative synthesis [ 10 , 13 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. We did not include the study of Villareal-Garza et al in the meta-analysis of non-pregnant women, because the study population was specifically women with breast cancer whereas the population of the remaining articles was made up of individuals without a specific pathology.…”
Section: Resultsmentioning
confidence: 99%
“…After the elimination of duplicate studies, we assessed the titles and abstracts of the 434 remaining studies, and 401 articles were eliminated because they did not match the selection criteria. A total of 33 studies were read in full-text and 19 studies were included in the qualitative synthesis and 18 in the quantitative synthesis [ 10 , 13 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. We did not include the study of Villareal-Garza et al in the meta-analysis of non-pregnant women, because the study population was specifically women with breast cancer whereas the population of the remaining articles was made up of individuals without a specific pathology.…”
Section: Resultsmentioning
confidence: 99%
“…We have reached the stage of the COVID-19 pandemic that encouraging mass COVID vaccination is very important, yet, there is reluctance in certain regions among the older people and their caregivers of receiving vaccination, in fear of the side effects. For example, a recent report from Colombia showed that only one-sixth of the caregivers of the elderly gave an opinion on acceptance of COVID-19 vaccination [4] . Hence passing on the right information about the benefit of vaccination is very important as well.…”
Section: Authors Contributionsmentioning
confidence: 99%
“…By the end of the 19th century and the beginning of the 20th, the discoveries of microorganisms that cause specific diseases (tuberculosis, cholera, diphtheria, tetanus, pneumonia, meningitis, syphilis, and others) and the identification of vectors capable of transmitting diseases (the Anopheles mosquito for malaria) [2] consolidated a new paradigm for the study of infectious diseases, their control and prevention [3]. In addition, with the development of vaccines and the emergence of antimicrobial therapy during the first half of the 20th century, we were excited about the disappearance of infectious diseases [4]. At least, that was the perception that high-income countries had during the 1960s and 1970s, especially inspired by the eradication of smallpox [5] and which, in some way, motivated the theory of epidemiological transition [6].…”
Section: Introductionmentioning
confidence: 99%